Making agriculture work for women: What has worked? - Rubin, Deborah (Technical Centre for Agricultural and Rural Cooperation, 2019)
Deborah Rubin presents an overview on the state of women in agribusiness in developing countries, with examples on what has worked in this area in the past years.